Issues and Advances in the Systematic Review of Single-Case Research: A Commentary on the Exemplars. (November 2017) - Manolov, Rumen; Guilera, Georgina; Solanas, Antonio
The current text comments on three systematic reviews published in the special section Issues and Advances in the Systematic Review of Single-Case Research: An Update and Exemplars . The commentary is provided in relation to the need to combine the assessment of the methodological quality of the studies included in systematic reviews, the assessment of the presence of functional relations via visual analysis following objective rules, and the quantification of the magnitudes of effect, providing meaningful information. Although it was not required that the exemplars follow specific guidelines for conduct and reporting, we applied an existing methodological quality checklist for systematic reviews and meta-analyses. Finally, we point at specific signs of advance in the field of performing systematic reviews of single-case design studies, as identified in the three exemplars, and we also suggest some issues requiring further research and discussion.